2018
DOI: 10.3390/ijms19030771
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Sensitizer Effects of Fenugreek Seeds in Parallel with Changes in Plasma MCH Levels in Healthy Volunteers

Abstract: In developed, developing and low-income countries alike, type 2 diabetes mellitus (T2DM) is one of the most common chronic diseases, the severity of which is substantially a consequence of multiple organ complications that occur due to long-term progression of the disease before diagnosis and treatment. Despite enormous investment into the characterization of the disease, its long-term management remains problematic, with those afflicted enduring significant degradation in quality-of-life. Current research eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 71 publications
0
10
1
1
Order By: Relevance
“…Effect of chronic diosgenin and fenugreek seed treatment on area under the glucose curve during ITT Our data showed that despite TFG enhanced weight gain and increased abdominal adiposity, parameters well connected to the development of insulin resistance, 6 weeks treatment with fenugreek seeds didn't alter insulin sensitivity. It is well established that fenugreek has an insulin sensitizing effect [4,5,15,25,30,31] and delays the development of glucose intolerance in sensitive patients, but our results with diosgenin could not corroborate this, which suggests that sapogenins do not play a significant role in the insulin sensitizing effect of TFG, and the applied dose of TFG is not enough to increase insulin sensitivity in the DIO model.…”
Section: Figurecontrasting
confidence: 78%
“…Effect of chronic diosgenin and fenugreek seed treatment on area under the glucose curve during ITT Our data showed that despite TFG enhanced weight gain and increased abdominal adiposity, parameters well connected to the development of insulin resistance, 6 weeks treatment with fenugreek seeds didn't alter insulin sensitivity. It is well established that fenugreek has an insulin sensitizing effect [4,5,15,25,30,31] and delays the development of glucose intolerance in sensitive patients, but our results with diosgenin could not corroborate this, which suggests that sapogenins do not play a significant role in the insulin sensitizing effect of TFG, and the applied dose of TFG is not enough to increase insulin sensitivity in the DIO model.…”
Section: Figurecontrasting
confidence: 78%
“…Desta forma, o pó de feno-grego é considerado um ingrediente funcional válido para reduzir a glicemia pós-prandial. Contribuindo com os resultados mostrados, no estudo citado Kiss, et al, (2018) se expôs que a preparação oral de sementes de feno-grego melhora o metabolismo da glicose por seu efeito sensibilizante à insulina e o aumento da sensibilidade à insulina associado ao feno-grego foi mais poderoso em pacientes com os mais baixos parâmetros basais na taxa de infusão de glicose.…”
Section: Resultsunclassified
“…Limited studies have investigated the effect of fenugreek on insulin levels and HOMA-IR and found non-signi cant reduction effects on these parameters. However, the estimated effect size of the pooled results of 4 [22,43,47,53] and 3 trials [43,47,53] that reported the effect of fenugreek on insulin levels and HOMA-IR respectively, showed signi cant reduction in insulin levels in intervention groups compared with placebo which can be partly due to its lowering effects on blood sugar levels and also indicates an increase in insulin sensitivity and a decrease in the need for more insulin secretion. HOMA-IR also decreased, although it was not signi cant.…”
Section: Discussionmentioning
confidence: 99%